Prospective Long-term Follow-up of Focused Ultrasound Unilateral Subthalamotomy for Parkinson Disease. (28th March 2023) - Martínez-Fernández, Raúl; Natera-Villalba, Elena; Máñez Miró, Jorge U.; Rodriguez-Rojas, Rafael; Marta del Álamo, Marta; Pineda-Pardo, José Ángel; Ammann, Claudia; Obeso, Ignacio; Mata-Marín, David; Hernández-Fernández, Frida; Gasca-Salas, Carmen; Matarazzo, Michele; et al.
Abstract : Background and Objectives: Unilateral magnetic resonance–guided focused ultrasound subthalamotomy (FUS-STN) has been shown to improve the cardinal motor features of Parkinson disease (PD). Whether this effect is sustained is not known. This study aims to report the long-term outcome of patients with PD treated with unilateral FUS-STN. Methods: We conducted a prospective open-label study of patients with asymmetrical PD who underwent unilateral FUS-STN. All patients were evaluated up to 36 months after treatment. The primary outcome was the difference from baseline to 36 months after FUS-STN in the score of the Movement Disorder Society–Unified Parkinson's Disease Rating Scale (MDS-UPDRS) motor part (III) for the treated hemibody in the off-medication state. The safety outcome included all adverse events occurring during follow-up. Secondary outcomes were the change in the MDS-UPDRS III score on-medication; subscores of rigidity, bradykinesia, tremor, and axial features; total MDS-UPDRS III; and the MDS-UPDRS part IV. Functional disability and quality of life were assessed using the MDS-UPDRS II and the PDQ39, respectively. Patient impression of change and satisfaction with the treatment were self-assessed. The Wilcoxon signed-rank test with subsequent Bonferroni's correction was used for data analysis. Results: Thirty-two patients with PD were evaluated at 36 months after treatment. The mean (±SD) age at baseline was 56.0 ± 10.1 years, with a mean disease duration of 6.8 ± 2.8 years. The MDS-UPDRS III score for the treated hemibody off-medication was improved by 52.3% from baseline to 3 years (score reduction from 19.0 ± 3.2 to 8.9 ± 3.3, 95% CI 8.7 to 11.6, p < 0.001), and all specific motor features were improved from baseline. No disabling or delayed adverse events were reported. The total MDS-UPDRS III off-medication score was 22.9% lower at 3 years than before treatment (36.8 ± 7.4 vs 27.4 ± 6.2, 95% CI 6.0 to 11.5, p < 0.001). The MDS-UPDRS II, IV, and PDQ39 scores and levodopa dose were equivalent to those at baseline. Discussion: The benefit of unilateral FUS-STN on PD motor features is sustained in the long term. FUS-STN contributes to better clinical control over several years of evolution. NCT02912871/03454425. Classification of Evidence: This study provides Class IV evidence on the utility of focused ultrasound unilateral subthalamotomy in the treatment of people with Parkinson disease.